Trichoderma asperellum efficiency in soybean yield components - Chagas, Lillian França Borges; Chagas Junior, Aloisio Freitas; Fidelis, Rodrigo Ribeiro; Carvalho Filho, Magno Rodrigues de; Miller, Luciane de Oliveira (Comunicata Scientiae, 2017)
The present study aimed to evaluate the Trichoderma asperellum inoculation efficiency in agronomic performance of soybean plants under field conditions. Two experiments were conducted in a savanna in Gurupi, Tocantins, Brazil, during the 2013/2014 and 2014/2015 crop years, being realized soil chemical analysis and recording the climatic conditions. For the experiment, seeds from the cultivar Monsoy 9144 RR were used and the inoculation with T. asperellum were carried out with a powdered product with active ingredient based on Trichoderma (Trichoderma asperellum - UFT201), formulated with minimum viable concentration of conidia of 2x109 g-1, applied directly on the seeds (20 g/kg seed), in one of the treatments. Were evaluated the biomass, relative efficiency, initial and final stand, effectiveness or efficiency in the use of T. asperellum in maintaining the stand and yield. It was observed that with the use of the treatment with T. asperellum inoculation, the yield of both harvests were 8.5 and 9.1% higher, respectively, when compared to the treatment with no inoculation.